Respuesta :
Answer:
9/4
Step-by-step explanation:
1 3/8 - (- 7/8)
1 3/8 + 7/8
9/4
Answer:
[tex] \frac{9}{4} [/tex]
Step-by-step explanation:
[tex]1 \frac{3}{8} - ( - \frac{7}{8} ) \\ \frac{1 \times 8 + 3}{8} = \frac{8 + 3}{8} = \frac{11}{8} \\ \frac{11}{8} - ( - \frac{7}{8} ) = \frac{11}{8} + \frac{7}{8} \\ \frac{11 + 7}{8} = \frac{18}{8} [/tex]
[tex]\boxed{\bold{Answer:{\boxed{\green{\bold{ =\frac{9}{4} }}}}}}[/tex]
┈➤ . . ⇢ ˗ˏˋ⌦ ..♡ˎˊ˗ ꒰✈꒱
╭─────────
┊╭─────────
┊✿꒷꒦ ♡◇♧♤
╰─────────
★ . ꜝꜞ ᳝ ࣪ hope that helped! ʬʬ